Data regarding country-specific variability in Covid-19 prevalence, incidence, and case fatality rate (2020)
This article contains data on country-specific variability in Covid-19 prevalence, incidence, and case fatality rate among the 238 countries globally. We used the World Health Organization worldwide Covid-19 tracking site to determine the number of confirmed Covid-19 cases, the number of fatalities attributed to Covid-19, and the case fatality rate for each of 238 countries. Using data from the United Nations Department of Economic and Social Affairs, we extracted key country-specific metrics with potential associations with Covid-19 including total population, land area, population density, percentage of residents living in urban areas, and median age. We extracted country-specific economic indicators from The World Bank Group Open Data database. All data were extracted on August 15, 2020. We developed consolidated data sets and calculated the country-specific point prevalence and incidence of Covid-19 and associated deaths. These data are associated with the article “Spatial Analysis of Global Variability in Covid-19 Burden”. Data are stored in a comma separated value format and can be downloaded from the Data in Brief website.